1985
DOI: 10.1007/bf01410386
|View full text |Cite
|
Sign up to set email alerts
|

Orientation analysis of uniaxially drawn polystyrene films doped with fluorescent molecules by fluorescence polarization, UV-and IR-dichroism and birefringence

Abstract: Atactic polystyrene (PS) is doped in solution with various fluorescent molecules and cast to fdms. Rectangular samples, cut from these films, are uniaxially drawn at 100 ~ and 110 ~ The orientation of the'fluorescent probes is characterized by UVdichroism and fluorescence polarization, that of the polymer segments by IR-dichroism and birefringence. It is observed that the fluorescent molecules depending on their structure tend to orientate more or less perpendicular to the drawing direction. This can be unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
1
6
1
Order By: Relevance
“…They concluded that the benzene rings of the probe molecules and of polystyrene may tend to associate mutually, which would be an energetic interaction. Nevertheless, results of Neuert et al 30 are in detail not in accordance with the data presented here. With their probe molecules ͑including 2b used in this contribution͒ Neuert et al determine negative values of ͗P 2 ͘ in the range down to Ϫ0.05 by UV-dichroism and fluorescence polarization.…”
Section: Stretched Polystyrene Filmscontrasting
confidence: 95%
See 1 more Smart Citation
“…They concluded that the benzene rings of the probe molecules and of polystyrene may tend to associate mutually, which would be an energetic interaction. Nevertheless, results of Neuert et al 30 are in detail not in accordance with the data presented here. With their probe molecules ͑including 2b used in this contribution͒ Neuert et al determine negative values of ͗P 2 ͘ in the range down to Ϫ0.05 by UV-dichroism and fluorescence polarization.…”
Section: Stretched Polystyrene Filmscontrasting
confidence: 95%
“…As the odfs in polystyrene show a different behavior it is supposed that special steric and energetic interactions between the phenyl rings of the guest molecules and PS influence the type of the odf. This result is in accordance with the explanation given by Neuert et al 30 for orientation of similar chromophores in PS. They concluded that the benzene rings of the probe molecules and of polystyrene may tend to associate mutually, which would be an energetic interaction.…”
Section: Stretched Polystyrene Filmssupporting
confidence: 94%
“…With increasing elongation of the film, the dye molecules orient more parallel to the elongation direction. This is interpreted as a steric interaction between the dye molecules and the polymer matrix, which causes the alignment of the rod-like dye molecules preferentially parallel to the stretched polymer chains. ,, The distribution of orientation angles φ is shown in Figure c,d. The average orientation is initially ⟨φ⟩ = 46.3° and changes during the elongation to ⟨φ⟩ = 24.8°.…”
Section: Resultsmentioning
confidence: 99%
“…The orientation degree f of the main chain was calculated using eqns and for orientational birefringence. For poly(3‐TFMSt), poly(4‐TFMSt), and poly(3,5‐BTFMSt), a symmetric stretching of the CH 2 group at a wavenumber of around 2840 cm −1 and an α of 70° was used . For poly(MMA‐co‐2‐TFMSt), the symmetrical bending vibration of the α ‐CH 3 group at a wavenumber of 1388 cm −1 and an α of 90° was used…”
Section: Methodsmentioning
confidence: 99%
“…For poly(3-TFMSt), poly(4-TFMSt), and poly (3,5-BTFMSt), a symmetric stretching of the CH 2 group at a wavenumber of around 2840 cm À1 and an α of 70°was used. [15] For poly(MMA-co-2-TFMSt), the symmetrical bending vibration of the α-CH 3 group at a wavenumber of 1388 cm À1 and an α of 90°was used. [16] Other measurements…”
Section: Infrared Spectroscopic Measurementsmentioning
confidence: 99%